The Impact of Effective Corporate Governance on The Quality of Financial Reports, Mediated by The Use of Information Technology - Putra, I Putu Mega Juli Semara; Juniariani, Ni Made Rai (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
Purpose—The paper aims to examine the impact of good corporate governance on the quality of financial reports using the mediation effect of information technology utilization. Methodology—This study was conducted in all Lembaga Perkreditan Desa (LPDs) in Bali. The study population included 1,334 LPDs based on data from Bali LP-LPDs as of 2022. The objects in this study include good corporate governance, the use of information technology, and the quality of LPD financial reports. The research sample was 299, which was determined based on a proportionate stratified random sampling design. Findings— The findings indicate that the use of sound corporate governance principles is very important to ensure better and more reliable financial report quality. The use of information technology is able to mediate the relationship between good corporate governance and the quality of financial reports. This shows that the application of information technology in an organization can act as a link between the tenets of effective corporate governance and the integrity of financial statements. Research limitations—The limitation of this study is that was conducted at LPDs in Bali, so caution is needed in generalizing the research results. The R Square value is 64.4%, so that indicates that there are numerous more elements influence the quality of financial reports. Paper type— research paper.